Hunting Territories, Hunting Bosses and Communal Production among Coastal James Bay Cree - Scott, Colin (Anthropologica, 2022)
This examination of the different productive activities of James Bay Cree hunters/trappers/fishermen indicates that fur production for the market fails to account for the presence or absence of the hunting territory-hunting boss complex. Indeed, this complex is not, as some earlier anthropologists believed, an instance of incipient private property or privatized usufruct. The hunting boss is a political leader and resource custodian, not a private owner. Cree hunting territories are consistent with the communal and egalitarian relations that dominate land-based production. This analysis supports the view that the territorial complex and its variations are adaptations anchored in Cree knowledge of the characteristics of game, including appropriate hunting and game management strategies.